Metaphorical Views of Physics Teachers in Teaching Physics: A Qualitative Phenomenological Study - Mae Anne Regero Migue (Alliance of Health Activists (AloHA), 2022)
Metaphors are words used to describe something or any situation that had happened. It can be used to replace an idea or concept to make a wider view of explaining the other idea and it an avenue for an individual to express what they say indirectly. Physics teachers nowadays faces a lot of struggles throughout their teaching experiences as they practice their profession. That’s why this qualitative phenomenological study aimed to understand the views and experiences of science teachers with regards to physics teaching. How do Physics teachers relate, take into account and express their views to physics teaching through the use of metaphors in describing their experiences. Teachers are the one with actual experiences with the students giving them a lot of struggles. Understanding how they feel through their experiences using metaphors could help design and carry out a good teaching and learning environment in Physics subject. This study gathered metaphorical views of Physics teachers about Physics teaching through the process called verbal protocol and was participated by seven Physics teachers who are currently taking up their master’s degree in Physics in Philippine Normal University and are also teaching Physics in their respective schools in Luzon. The data gathered were analysed through metaphorical analysis and the results revealed that there are different factors affecting the views of the teachers towards teaching Physics. There are also categories of the metaphors used by the teachers in describing their views towards Physics teaching wherein they considered teaching Physics as a teaching career that let them undergo difficulties and challenges. It is also a teaching that needs passion and goal to let students understand abstract ideas that involves logical mathematical concepts that they considered difficult. Physics teaching also is considered a happy and sad experience for the teacher and it needs labor and patience. Keywords: metaphorical views; physics teaching; metaphors